Enhancing Elementary Science Learning: Development of Animated Video Media for Water Cycle Education - Yusni Arni; Muhammad Khoirul Anan; Imam Wijaya; Muhammad Ichsanudin Abdillah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Technological advancements significantly impact the learning process, requiring teachers to develop interactive and engaging educational media. This study aims to create an animated video about the water cycle to enhance students' understanding and make learning more appealing. The research employed the ADDIE development model, which consisted of the analysis, design, development, implementation, and evaluation phases. Validation of the media and material was conducted using a Likert scale instrument through feedback from a teacher at SDN 226 Palembang. The assessment scaled from 2.0 (not feasible) to 3.5 (very feasible). The animated video received a media validation score of 3.6 and a material validation score of 3.7, both categorized as feasible for educational use. The findings indicate that the animated water cycle video is highly suitable for elementary school applications. It effectively supports teachers by visually presenting the water cycle process, enhances student comprehension, and contributes to a more dynamic and engaging learning environment.